PROSPECTIVE STUDY ON THE DEVELOPMENT OF ALLOIMMUNE THROMBOCYTOPENIA IN NEONATES BORN TO MOTHERS WITH ANTI-HPA-4B - Yosimatu, Nobuhiro; Ohsugi, Kazuo; Ishijima, Ayako; Takasaki, Katsunori; Fujimori, Keiya; Enomoto, Takayuki; Azuma, Tatsuro; Sato, Akira; Yamaguchi, Osamu; Tohyama, Yuriko; Hando, Keiichi; Imamura, Shinya; et al. (Journal of the Japan Society of Blood Transfusion, 2000)
Among the 21, 354 pregnant women studied, anti-HPA-4b was detected in 39 (0.18%), and 6 neonates developed neonatal alloimmune thrombocytopenia (NAIT; platelet count<15×104/μl). Platelet count at delivery was significantly different between neonates compatible (27.0×104/μl) and incompatible (15.3×104/μl, p<0.05) with maternal anti-HPA-4b. However, no significant difference between maternal anti-HPA-4b titer and the platelet count of incompatible neonates was observed. High titer (>64) of anti-HPA-4b, however, was associated with a higher risk of NAIT. In addition, normalization of platelet count (>15×104/μl) was delayed in babies from mothers with high antibody titer (>64) compared with babies from women with low antibody titer (≤64).